Pengaruh Media Manipulatif Terhadap Minat Belajar Siswa Pada Pembelajaran Tematik Kelas 1 SD Negeri 62 Sungai Raya - Nadia, Asma; Afryaningsih, Yunika; Purwaningsih, Dewi Ismu (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
This study aims to describe the effect of manipulative media on students’ learning interest in thematic learning class 1 of SD Negeri 62 Sungai Raya. The method used is the experimental method, while the research design used is a quasi-experimental design. The independent variable (X) in this study is the influence of manipulative media, while the dependent variable (Y) is learning interest. The population included in this study were students in class 1 A as the control class and class 1 B as the experimental class at SD Negeri 62 Sungai Raya. Class A has 18 students consisting of 12 male students and 6 female students. Meanwhile, class 1 B has 18 students consisting of 9 male students and 9 female students. The sample in this study were students in class 1 B (experimental class) and 1 A (control class) of SD Negeri 62 Sungai Raya. The technique used to determine the experimental and control classes uses simple random sampling. In data collection, researchers used observation sheets and questionnaires. Based on the results of the T-test the effect of manipulative media on learning interest. Through the normality test and homogeneity test first, then the t test was carried out which obtained the post-test test scores for the experimental class and the control class, obtained tcount and ttable 1.691 (α ₌ 5%, dk ₌ 18 + 18 – 2 = 34) equal to . Because tcount 2.849 > ttable 1.691, then Ha is accepted. So, it can be concluded that there is significant influence and difference between the experimental class that uses manipulative media and the control class does not use manipulative media.